Biopolymer‐based Carriers for DNA Vaccine Design. Issue 24 (7th January 2021) - Franck, Christoph O.; Fanslau, Luise; Bistrovic Popov, Andrea; Tyagi, Puneet; Fruk, Ljiljana
Abstract: Over the last 30 years, genetically engineered DNA has been tested as novel vaccination strategy against various diseases, including human immunodeficiency virus (HIV), hepatitis B, several parasites, and cancers. However, the clinical breakthrough of the technique is confined by the low transfection efficacy and immunogenicity of the employed vaccines. Therefore, carrier materials were designed to prevent the rapid degradation and systemic clearance of DNA in the body. In this context, biopolymers are a particularly promising DNA vaccine carrier platform due to their beneficial biochemical and physical characteristics, including biocompatibility, stability, and low toxicity. This article reviews the applications, fabrication, and modification of biopolymers as carrier medium for genetic vaccines. Abstract : Recently, the first genetic vaccine has been approved to tackle the COVID‐19 pandemic. Despite their favourable properties, low transfection efficacies prevent many nucleic acid vaccines from being approved for human use. This Review explores strategies that use biopolymeric delivery systems to improve the efficacy of DNA immunisation.